Jutro: posthumanistyczny przekład artystyczny - Tamara Brzostowska-Tereszkiewicz (Ksiegarnia Akademicka Publishing, 2018)
Tomorrow: Post-Humanist Artistic Translation The Polish translation of Alfred Jarry’s Ubu Roi carried out by means of Google Translate and published by Piotr Marecki and Aleksandra Małecka in the Conceptual Line series (Ha!art Corporation, 2015) prompts theoretical reflections on the semantic value and artistic potential of machine (“non-subjective”) translation. It also allows for a revision of the existing hypotheses of historians, theoreticians, critics, and practitioners of literary translation regarding the role of the translator in interlingual and intercultural communication.